Uniport Versus Multiport Video Assisted Thoracoscopic Surgery (VATS): Comparisons and outcomes: A Review Article - Pavel M. Kareem; Sanna O. Karim; Hawar A. Sofi; Fuad Emad Fuad; Suhaib H. Kakamad; Hiwa O. Abdullah; Berun A. Abdalla; Shavn M. Hussein; Hawbash M. Rahim; Marwan N. Hassan; Fahmi H. Kakamad; Hiwa A. Ali (Barw Medical Journal, 2023)
Abstract There are contr oversies regarding the number of ports in video-assisted thoracoscopic surgery (VATS). The aim of this review is to compare the outcomes of multiport VATS and uniport VATS in form of postoperative pain, hospital stay, the volume of blood loss, duration of operation, duration of postoperative drainage and conversion rate. Although lacks a high level of evidence, this short review showed that uniport VATS might be a preferred alternative approach in thoracic surgery. Patients with uniport VATS have shorter hospital stays, less pain, early recovery and sooner removal of the chest tube.